Following the Crowd: Leisure Complementarities beyond the Household - Georges-Kot, Simon; Goux, Dominique; Maurin, Eric (Journal of Labor Economics, 2017)
Leisure externalities across households have important implications for labor market regulations but have proven very difficult to identify. This paper exploits the unique features of school holidays and paid leave regulations in France to show that exogenous increases in the amount of leisure time enjoyed by workers living with children induce very significant increases in the demand for leisure of workers living in other households. We also provide evidence that these cross effects are driven by complementarities in nonmarket time rather than workplace norms or workplace externalities.